PREDIKSI SENYAWA EUCALYPTUS SEBAGAI INHIBITOR POTENSIAL COVID-19 MAIN PROTEASE (Mpro) SECARA MOLECULAR DOCKING - Muhammad Fauzi; Fauzi Rahman; Yulistia Budianti Soemari; Richa Purnamasari (Universitas Islam Kalimantan Muhammad Arsyad Al Banjari, 2021)
The development of cases infected with the COVID-19 virus in Indonesia continues to increase. COVID-19 is a member of the corona virus family that has spread throughout the world. The COVID-19 Main protease is considered a suitable target for drug design against SARS infection because it plays a role in the processing of polyproteins required for the reproduction of the coronavirus. Eucalyptus are claimed to be able to ward off the COVID-19 virus. Therefore it is necessary to evaluate the content of eucalyptus compounds against Main proteases by docking studies. Based on the results of research conducted using the active site on the Main protease, it is known that eucalyptus (-)-globulol, epiglobulol, and ledol compounds have free energies of -7.23 kcal/mol, -7.91 kcal/mol, and -7.39 kcal/mol, respectively. Remdesivir as a therapeutic drug for COVID-19 has a free energy of -7.67 kcal/mol. These three compounds bind to the amino acid Glu166 as remdisivir with the best binding affinity on the active site of the Main protease. So these three compounds have the potential to inhibit the COVID-19 virus.